Developments in bitumen emulsion mixtures for roads - Needham, D. (1996)
Bitumen emulsion mixtures, or cold mix, offers certain advantages over hot bituminous road mixtures in terms of potential cost savings, environmental factors, energy savings and easing of logistical difficulties inherent with hot mix. For these reasons, they are currently used in a number of regions including the United States of America, Continental Europe, Scandinavia, Southern Africa and Australia. However, cold mix has not been seriously evaluated or utilized in the UK until comparatively recently. This is due to the slow rate at which it builds strength or cures and its susceptibility to rainfall, particularly during this curing period. The overall aim of this research was, therefore, to study the behaviour of cold mix in terms of mechanical properties and the mechanisms involved in emulsion breaking and mixture curing to gain an insight into how performance may be improved.